CCN2 Aggravates the Immediate Oxidative Stress–DNA Damage Response following Renal Ischemia–Reperfusion Injury - Floris A. Valentijn; Sebastiaan N. Knoppert; Georgios Pissas; Raúl R. Rodrigues-Diez; Laura Marquez-Exposito; Roel Broekhuizen; Michal Mokry; Lennart A. Kester; Lucas L. Falke; Roel Goldschmeding; Marta Ruiz-Ortega; Theodoros Eleftheriadis; et al. (Antioxidants, 2021)
AKI, due to the fact of altered oxygen supply after kidney transplantation, is characterized by renal ischemia–reperfusion injury (IRI). Recent data suggest that AKI to CKD progression may be driven by cellular senescence evolving from prolonged DNA damage response (DDR) following oxidative stress. Cellular communication factor 2 (CCN2, formerly called CTGF) is a major contributor to CKD development and was found to aggravate DNA damage and the subsequent DDR–cellular senescence–fibrosis sequence following renal IRI. We therefore investigated the impact of CCN2 inhibition on oxidative stress and DDR in vivo and in vitro. Four hours after reperfusion, full transcriptome RNA sequencing of mouse IRI kidneys revealed CCN2-dependent enrichment of several signaling pathways, reflecting a different immediate stress response to IRI. Furthermore, decreased staining for γH2AX and p-p53 indicated reduced DNA damage and DDR in tubular epithelial cells of CCN2 knockout (KO) mice. Three days after IRI, DNA damage and DDR were still reduced in CCN2 KO, and this was associated with reduced oxidative stress, marked by lower lipid peroxidation, protein nitrosylation, and kidney expression levels of Nrf2 target genes (i.e., HMOX1 and NQO1). Finally, silencing of CCN2 alleviated DDR and lipid peroxidation induced by anoxia-reoxygenation injury in cultured PTECs. Together, our observations suggest that CCN2 inhibition might mitigate AKI by reducing oxidative stress-induced DNA damage and the subsequent DDR. Thus, targeting CCN2 might help to limit post-IRI AKI.